A noção de variável de alunos do ensino fundamental - MIRANDA, Tatiana Lopes de (Universidade Federal do Pará, 2017)
The present study deals with the algebraic school education, having as main objective the search for a description of the concept of variable, by solving problems for students who are in elementary school. There was variable notions that appear in the teaching and learning of school algebra process that allowed to answer the following questions: What are the elements that constitute the variable notions are perceived by students in order to provide them with a greater understanding of school algebra? How to identify these elements in the school environment allows us to propose a description for algebra in elementary school? To achieve the objective, the research was divided into two phases. In the first phase of the study, was adopted as a methodological approach to bibliographic search, based on historical research into the development of algebra and its teaching in the context of mathematics education, in order to study the evolution of the concept of algebra and variable along the story and identify the notions of variable described in the research area of mathematics education. Among the theoretical frameworks are worked Tabak (2004), Wussing (1998), Boyer (2012), Kieran (1989), Usiskin (1995), Ursini and Trigueros (2003), among others. Based on reference chosen was structured fieldwork, which constituted the second phase of the study, which it presented as a diagnostic tool for data collection three questionnaires, each one composed of 10 questions, which were applied for 65 students who attended the 9th year of primary school in three public schools in the city of Belém (PA). The questionnaires helped identify the notions of variable and the elements of these notions present in the classroom. The results show that students have not mastered all the concepts of variable that were classified in our theoretical framework. It was found that the notion of variable as unknown, it shows greater role for students, however, realizes that what constitutes this and other notions concerning the handling, symbolization and interpretation, represent obstacles to understanding the thinking and language of algebra.